Pengaruh Jumlah Kunjungan Wisatawan terhadap Pendapatan Asli Daerah Kota Palembang Melalui Pajak Hotel Sebagai Variabel Intervening - Sari, Mei; Sari, Rafika; Munandar, Aris (Universitas Batanghari Jambi, 2024)
This research aims to determine the influence of the number of tourist visits on the regional original income of Palembang City through hotel taxes as an intervening variable. The type of research used is quantitative research with the data used is secondary data. Sampling in this research used a saturated sampling technique which used the entire population, namely 48 months of data. The data collection technique in this research is documentation carried out at the Regional Revenue Agency of Palembang City, the Tourism Office and the Regional Financial & Asset Management Agency of Palembang City. The results of this research state that the number of tourist visits has no effect on the local income of the city of Palembang, the number of tourist visits has an effect on hotel tax, the hotel tax has no effect on the local income of the city of Palembang. Meanwhile, it is known that the value of the indirect effect is 0.191 and the direct effect is 0.286 which means the direct influence value is greater than the indirect influence value and it can be concluded that the number of tourist visits has no effect on the regional original income of Palembang City through hotel tax as an intervening variable.